Market reaction to the rights issue announcement on the Indonesia stock exchange - Dewi, Ni Putu Linsia; Candraningrat, Ica Rika (International research journal of management, IT and social sciences, 2019)
Rights issue or the issuance of pre-emptive rights are the rights granted by an issuer company made to its existing shareholders to buy new shares issued within a predetermined period of time. This study aims to empirically explain the differences in abnormal returns before and after the announcement of the rights issue and to determine the form of capital market efficiency in Indonesia. Data are collected from 27 listed companies in the Indonesia Stock Exchange (IDX) that conducted a rights issue in 2014-2018. The data analysis technique used is the Kolmogorov-Smirnov Normality Test and the Parametric Statistical Test with a paired sample t-test. Based on the results of hypothesis testing not found differences in abnormal returns both before and after the announcement date indicating the market does not react to the right issue event. The results of statistical tests show a downward trend of abnormal return which is proxied in the Cumulative Abnormal Return (CAR), implying a market tends to react negatively to the announcement of the rights issue. Rights issue information causes a new equilibrium price adjustment in the market, thus making the form of efficiency of the Indonesian capital market a semi-strong form.